(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The fruits and vegetables processing industries have tremendous potentials in creating income and employment for rural labour-force. This study is concerned with the problems and prospects of the cluster of onion dehydration enterprises located in Mahuva taluka Bhavnagar district of Gujarat state in India. This paper is regarding contribution of onion dehydration firm in Indian Economy. We wish to discuss about types of different product produced in large amount by onion dehydration firm, on the basis of primary data.